Tinjauan Ketepatan Kode Cedera Multiple Pada Kasus External Cause di RSUP Dr. M. Djamil Padang - Oktamianiza Oktamianiza; Diah Salsa Billa; Kalasta Ayunda Putri; Yulfa Yulia; Afridon Afridon (Poltekkes Kemenkes Semarang, 2023)
The accuracy of the code is very necessary so that the information generated from the diagnosis and medical treatment is accurate. However, researchers found in Dr. M. Djamil Padang there are still 29 incorrect codes (76.3%). This is because the determination of multiple injury codes is written separately and fracture diagnosis is not equipped with a fifth character code. The purpose of this study was to determine the accuracy of multiple injury codes in external cause cases at RSUP Dr. M. Djamil Padang. This research was conducted from May to June 2022. The type of research conducted was quantitative with a descriptive approach. The number of samples was 38 using the purposive sampling method, the data collection instrument used a checklist table with univariate analysis. The results of the research that has been carried out found that the frequency of diagnostic accuracy is 27 (71.1%) incorrect diagnoses, the frequency of conformity of primary and secondary diagnoses is 19 (50.0%) incorrect diagnoses, and the frequency of accuracy of diagnostic codes is 29 (76, 3%) code is not correct. So it can be concluded that there are still causes of inaccuracy in coding, which can be seen from the 3 components of the analysis carried out that affects the accuracy of the code. Therefore, researchers suggest that coders should pay attention to the rules and procedures for coding diagnoses based on ICD-10.